2015
DOI: 10.1016/j.foodchem.2014.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination and characterisation of extra virgin olive oils from three cultivars in different maturation stages using Fourier transform infrared spectroscopy in tandem with chemometrics

Abstract: A methodology based on Fourier transform infrared (FTIR) spectroscopy, combined with multivariate analysis methods, was applied in order to monitor extra virgin olive oils produced from three distinct cultivars on different maturation stages. For the first time, this kind of methodology is used for the simultaneous discrimination of the maturation stage, and different cultivars. Principal component analysis and discriminant analysis were utilised to create a model for the discrimination of olive oil samples. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 26 publications
2
60
1
Order By: Relevance
“…In fact, several research works have shown the efficiency of this technique for distinct determinations in olive oils, such as geographical origin or cultivars used, besides the detection of possible adulterations . Furthermore, in recent years the joint application of FTIR analysis and multivariate determinations has emerged as an interesting approach that allows the determination of several chemical parameters of olive oil, such as fatty acids, peroxide values, acidity, phenolic and volatile compounds, freshness, and oxidized fatty acids …”
Section: Introductionmentioning
confidence: 99%
“…In fact, several research works have shown the efficiency of this technique for distinct determinations in olive oils, such as geographical origin or cultivars used, besides the detection of possible adulterations . Furthermore, in recent years the joint application of FTIR analysis and multivariate determinations has emerged as an interesting approach that allows the determination of several chemical parameters of olive oil, such as fatty acids, peroxide values, acidity, phenolic and volatile compounds, freshness, and oxidized fatty acids …”
Section: Introductionmentioning
confidence: 99%
“…In addition, it has recently been used in the control of honeys' sugar concentration (Anjos, Campos, Ruiz, & Antunes, 2015) and in olive oil characterisation (Gouvinhas, de Almeida, Carvalho, Machado, & Barros, 2015). Despite the increasing interest and the recent developments, few studies focus on the use of FTIR-ATR for the quality control of grape-derived distillates (grape marc spirits, wine spirits and brandies).…”
Section: Introductionmentioning
confidence: 99%
“…Despite some studies performed on the identification of compound using few combination of chemometric techniques such as hierarchical cluster analysis [24], PCA, partial least square (PLS) and factor discriminant analysis (FDA) [25], the application of PCA into the characterization model has not been undertaken yet.…”
Section: Astesj Issn: 2415-6698mentioning
confidence: 99%